„Odmówił powrotu do kraju” – ucieczki piłkarzy z PRL na Zachód - Pilarski, Sebastian (Pamięć i Sprawiedliwość, 2014)
Illegal emigrations of football players from the People’s Republic of Poland were quite frequent, but in most cases they were not treated as high profile in the mass media. The only exception was the 1988 escape of Andrzej Rudy, a player in Poland’s national football team. The examples of emigrating athletes discussed in the text have been divided into two categories: defectors per se (those who left their teams’ foreign training camps), and people who refused to go back to Poland after legally obtaining a consent to travel to a Western country (or Yugoslavia). The first case of an athlete illegally leaving Poland took place in the 1950s, while the last one in the last months of the break-through year of 1989. It was usually footballers playing for Silesian clubs who opted for illegal emigration to West Germany. Family reasons were often quoted as a basis for making such a decision – numerous defectors were able to prove their German roots. The 1980s saw a particular intensification of escapes, which was related both to deteriorating economic conditions in Poland and more liberal passport policies at the end of the decade. It is worth noting that the communist authorities changed their attitude towards the phenomenon. While in the 1960s the secret police would keep the defectors and their families under surveillance, 20 years later the government would simply register anyone “refusing to return to Poland”.